Micro Teaching: Blood Donation (Kursus Sijil Pengajaran & Pembelajaran USM 2015) - Gen Thinker, Group 2; Mohamed Fauzi, Hafizuddin (P&P Courses, 2015)
Objectives: 1. students are know the basic eligible criteria for blood donation. 2. students are know the process of blood donation. 3. students are able to list the 4 types of blood group in a population. 4. students are able appreciate the important of blood to the patients need.